Big data for omni-channel supply chain management: the need for greater focus on people and process. (2016) - Roberts, Matthew; Hazen, Benjamin
Omni-channel retailing is reshaping consumers' purchasing experiences, and expectations. Supply chain management plays a large role in enabling this experience, where big data is used to optimise fulfilment and other key functions. While discussions on the role of big data in support of supply chain management have centred upon the technological aspects required to enable these functions, less attention has been paid to important people and process aspects. The purpose of this conceptual paper is to demonstrate the need for a broader discussion of the people and process aspects of big data employment for supply chain management in general and omni-channel in particular. These two dimensions are described in greater detail, and areas for further research are identified.